Carbon cycling in Arctic lakes: sedimentary biomarker reconstructions from Disko Island, West Greenland - Stevenson, Mark Andrew (2017)
A palaeolimnological study of three lakes on Disko Island, West Greenland was conducted across a hydrogeomorphic landscape gradient, to reconstruct principally changes in algal pigments, lipid biomarkers and carbon isotopes (δ13C) to investigate carbon cycling at multiple scales and resolutions. All three records reconstructed recent change on Disko, with records from lake Disko 2 additionally spanning since ~7640 cal. yr BP and lake Disko 4 since ~1260 cal. yr BP. Changes in sedimentary proxies were broadly consistent with the spatially and temporally heterogeneous environmental change known to have occurred across the Arctic over these periods, including recent warming (RW), the Little Ice Age (LIA) and the Medieval Climate Anomaly (MCA). However, the individual lake responses to these changes were highly landscape specific. Changes in algal pigments were linked to variations in the inputs of nutrients and DOC from soil microbial activity, variations in permafrost melt regime and glacier melt.